Irregular migrants in Belgium and the Netherlands : aspirations and incorporation - Meeteren, Masja van (IMISCOE research., 2014)
Proposing an empirically grounded theoretical critique of the dominant research practice that focuses on survival strategies, van Meeteren takes irregular migrants aspirations as a starting point of analysis. Drawing on intensive participant observation, as well as more than 200 in-depth interviews with irregular migrants and representatives of organisations working with them, she develops much-needed contextualised insights and sheds new light on earlier debates on this top-of the-agenda subject area.